Analysis of Internal and External Factors Causing Non-Performing Financing (NPF) in Islamic Banks in Indonesia - Andrina Sabariah (Jurnal Indonesia Sosial Sains, 2026)
Non-Performing Financing (NPF) is a major issue facing Islamic banking in Indonesia, potentially impacting business performance, stability, and sustainability. This study aims to analyze the internal and external factors that contribute to NPF and examine the control mechanisms and financing risk mitigation strategies in Islamic banking. A qualitative approach, using a literature study, was used, through secondary data analysis sourced from Financial Services Authority (OJK) reports, laws and regulations, and relevant scientific journals. The study results indicate that NPF is influenced by internal factors, such as the quality of financing analysis, risk management, contract structure, and customer understanding of Islamic financing products, as well as external factors such as economic conditions, competition between financial institutions, and regulatory changes. NPF control is achieved through the implementation of risk management, encompassing a structured process of risk identification, measurement, monitoring, and control, with the active involvement of management and the Sharia Supervisory Board. This study emphasizes the importance of strengthening comprehensive and adaptive financing risk management to reduce NPF levels and maintain the stability of Islamic banking in Indonesia.